Vitamin D Deficiency and Air Pollution Exacerbate COVID-19 Through Suppression of Antiviral Peptide LL37 - Crane-Godreau, Mardi A.; Clem, Kathleen J.; Payne, Peter; Fiering, Steven (Frontiers in Public Health, 2020)
Abstract: Vitamin D deficiency and insufficiency (VDD) are widely recognized as risk factors for respiratory tract infections. Vitamin D influences expression of many genes with well-established relevance to airway infections and relevant to immune system function. Recently, VDD has been shown to be a risk factor for acquisition and severity of COVID-19. Thus, treating VDD presents a safe and inexpensive opportunity for modulating the severity of the disease. VDD is common in those over 60 years of age, people of color and many with co-morbid conditions. Exposure to fine particulate air pollution is also associated with worse outcomes from COVID19. Vitamin D stimulates transcription of cathelicidin which is cleaved to generate LL37. LL37 is an innate antimicrobial with demonstrated activity against a wide range of microbes including envelope viruses. LL37 also modulates cytokine signaling at the site of infections. Fine particles in air pollution can interfere with LL37 destruction of viruses and may reduce effective immune signaling modulation by LL37. While vitamin D influences transcription of many immune related genes, the weakened antimicrobial response of those with VDD against SARS-Cov-2 may be in part due to reduced LL37. Conclusion: Vitamin D plays an important role reducing the impact of viral lung disease processes. VDD is an acknowledged public health threat that warrants population-wide action to reduce COVID-19 morbidity and mortality. While vitamin D influences transcription of many immune related genes, the weakened antimicrobial response of those with VDD against SARS-Cov-2 may be in part due to reduced LL37. Action is needed to address COVID-19 associated risks of air pollution from industry, transportation, domestic sources and from primary and second hand tobacco smoke.